A polymorphism in the haptoglobin, haptoglobin related protein locus is associated with risk of human sleeping sickness within Cameroonian populations. - Elvis Ofon; Harry Noyes; Julius Mulindwa; Hamidou Ilboudo; Martin Simuunza; Vincent Ebo'o; Flobert Njiokou; Mathurin Koffi; Bruno Bucheton; Pythagore Fogue; Christiane Hertz-Fowler; Annette MacLeod; et al. (Public Library of Science (PLoS), 2017)
Human African Trypanosomiasis (HAT) is a neglected disease targeted for elimination as a public health problem by 2020. Elimination requires a better understanding of the epidemiology and clinical evolution of HAT. In addition to the classical clinical evolution of HAT, asymptomatic carriers and spontaneous cure have been reported in West Africa. A genetic component to human susceptibility to HAT has been suggested to explain these newly observed responses to infection. In order to test for genetic associations with infection response, genetic polymorphism in 17 genes were tested (APOL1, IL1B, IL4, IL4R, IL6, IL8, IL12B, IL12RB1, IL10, TNFA, INFG, MIF, HLA-G, HLA-A, HP, HPR and CFH).A case-control study was performed on 180 blood samples collected from 56 cases and 124 controls from Cameroon. DNA was extracted from blood samples. After quality control, 25 samples (24 controls and 1 case) were eliminated. The genotyping undertaken on 155 individuals including 55 cases and 100 controls were investigated at 96 loci (88 SNPs and 8 indels) located on 17 genes. Associations between these loci and HAT were estimated via a case-control association test.Analyses of 64 SNPs and 4 indels out of 96 identified in the selected genes reveal that the minor allele (T) of rs8062041 in haptoglobin (HP) appeared to be protective against HAT (p = 0.0002395, OR 0.359 (CI95 [0.204-0.6319])); indicating higher frequency in cases compared to controls. This minor allele with adjusted p value of 0.0163 is associated with a lower risk (protective effect) of developing sleeping sickness.The haptoglobin related protein HPR and HP are tightly linked and both are duplicated in some people and may lead to higher activity. This increased production could be responsible of the protection associated with rs8062041 even though this SNP is within HP.